Secondary maternal-fetal consequences to electrical injury: A literature review - J.A. Caballero-Carvajal; E.F. Manrique-Hernández; C. Becerra-Ar; J.L. Alvarado-Socarras (Elsevier, 2020)
Electrical injuries can occur in pregnant women but currently their incidence is not completely known. Notwithstanding, those represent clinical important events such maternal and fetal death, which can be avoided if properly managed. The objective of this paper is to describe the results of electrical injury (high and low voltage), in pregnant women in scientific reports. A systematic search was performed with keywords "electrical injuries", "lightning injuries", "lightning strike", "pregnant women" and "pregnancy", using the databases: MedLine, Scielo, Lilacs, Clinical key, Web of Science, Scopus, Springer, Science Direct, Embase and Medic Latina. Filters like language, time, design and availability of text were not used. Descriptive analyses were carried out for variables such as maternal-fetal consequences, voltage and type of exposure, based on the reports identified. From the total 74 cases identified, 71.1% survived after the exposition. From the total live-births 28.6% did not show any alteration, 7.1% presented maceration and burns, while 64.3% had another outcome. Electric injury leads to fetal compromise and death in exposed pregnant women, mainly in the first hours after the injury. However, monitoring should be continued for the risk of complications such as placenta abruption, oligohydramnios and fetal distress. It is possible an underreporting of these events. Keywords: Electric injuries, Lightning injuries, Lightning stroke, Pregnancy, Pregnant women